O003 Saliva use as a lubricant for anal sex is a risk factor for rectal gonorrhoea among men who have sex with men, a new public health message: a cross-sectional survey. (30th June 2016) - Chow, Eric PF; Cornelisse, Vincent J; Read, Tim RH; Lee, David M; Walker, Sandra; Hocking, Jane S; Chen, Marcus Y; Bradshaw, Catriona S; Fairley, Christopher K
Abstract : Background/introduction: Apart from penile–anal intercourse, other anal sexual practices (oral-anal contact or rimming, fingering and saliva use as a lubricant for anal sex) are common among men who have sex with men (MSM). Aim(s)/objectives: The aim of this study is to evaluate whether these anal sexual practices are risk factors for rectal gonorrhoea in MSM. Methods: A cross-sectional survey was conducted among MSM attending a large urban sexual health centre between July 2014 and June 2015. Rectal gonorrhoea cases were identified by culture. Results: Among 1312 MSM, 4.3% (n = 56) had rectal gonorrhoea. Anal sexual practices, other than anal-penile sex, were common among MSM: receptive oro-anal (rimming) (70.5%), receptive fingering or penile-perianal contact i.e dipping (84.3%) and using partner's saliva as a lubricant for anal sex (68.5%). Saliva as a lubricant (adjusted OR 2.17; 95% CI 1.00 to 4.71) was significantly associated with rectal gonorrhoea after adjusting for potential confounding factors. Receptive rimming and fingering or penis dipping were not statistically associated with rectal gonorrhoea. The crude population attributable fraction of rectal gonorrhoea associated with use of partner's saliva as a lubricant for anal sex was 48.9% (7.9% to 71.7%). Discussion/conclusion: Saliva use as a lubricant for anal sex is a common sexual practice in MSM, and may play an important role in gonorrhoea transmission. Almost half of rectal gonorrhoea cases may be eliminated if a message of prevention is included in not using partner's saliva for anal sex.